Non-technical skills assessment scale in nursing: construction, development and validation - Sara Martins Pereira Pires; Sara Otília Marques Monteiro; Anabela Maria Sousa Pereira; Joana Novaes Machado Stocker; Daniela de Mascarenhas Chaló; Elsa Maria de Oliveira Pinho de Melo (Universidade de São Paulo, 2018)
ABSTRACT The introduction of non-technical skills during nursing education is crucial to prepare nurses for the clinical context and increase patient safety. We found no instrument developed for this purpose. Objectives: to construct, develop and validate a non-technical skills assessment scale in nursing. Method: methodological research. Based on the literature review and experience of researchers on non-technical skills in healthcare and the knowledge of the principles of crisis resource management, a list of 63 items with a five-point Likert scale was constructed. The scale was applied to 177 nursing undergraduate students. Descriptive statistics, correlations, internal consistency analysis and exploratory factor analysis were performed to evaluate the psychometric properties of the scale. Results: scale items presented similar values for mean and median. The maximum and the minimum values presented a good distribution amongst all response options. Most items presented a significant and positive relationship. Cronbach alpha presented a good value (0.94), and most correlations were significant and positive. Exploratory factor analysis using the Kaiser-Meyer-Olkin test showed a value of 0.849, and the Bartlett's test showed adequate sphericity values (χ2=6483.998; p=0.000). One-factor model explained 26% of the total variance. Conclusion: non-technical skills training and its measurement could be included in undergraduate or postgraduate courses in healthcare professions, or even be used to ascertain needs and improvements in healthcare contexts.